Effects and Feasibility of the "Traffic Light Method for Somatic Screening and Lifestyle" in Patients With Severe Mental Illness: A Pilot Study. Issue 2 (16th April 2014) - van Meijel, Berno; van Hamersveld, Sonja; van Gool, Ronald; van der Bijl, Jaap; van Harten, Peter
<x xml:space="preserve">Abstract</x> Purpose To study the preliminary effects and feasibility of the "Traffic Light Method for somatic screening and lifestyle" (TLM) in patients with severe mental illness. Design and Methods A pilot study using a quasi‐experimental mixed method design with additional content analyses of lifestyle plans and logbooks. Findings Significant improvements were found in body weight and waist circumference. Positive trends were found in patients' subjective evaluations of the TLM. The implementation of the TLM was considered feasible. Practice Implications The TLM may contribute to a higher quality of care regarding somatic screening and lifestyle training.